A twisted intramolecular charge transfer probe for rapid and specific detection of trace biological SO2 derivatives and bio-imaging applications. Issue 6 (2nd December 2014) - Zhu, Leiming; Xu, Junchao; Sun, Zhe; Fu, Boqiao; Qin, Caiqin; Zeng, Lintao; Hu, Xichao
Abstract : A highly "reactive" probe showed a ratiometric fluorescence response to HSO3 − with fast response and low detection limit (3.0 nM). Abstract : We reported a reactive probe for HSO3 −, which showed a colorimetric and ratiometric fluorescence response to HSO3 − with fast response ( t 1/2 = 20 s), good specificity and low detection limit (3.0 nM). The probe was cell membrane permeable and successfully used for visualizing trace SO2 derivatives in living cells.